Determination of CD43 and CD200 surface expression improves accuracy of B‐cell lymphoma immunophenotyping. Issue 6 (27th July 2020) - Hoffmann, Joerg; Rother, Marissa; Kaiser, Ulrich; Thrun, Michael C.; Wilhelm, Christian; Gruen, Andrea; Niebergall, Ute; Meissauer, Ute; Neubauer, Andreas; Brendel, Cornelia
Abstract: Background: The Matutes score (MS) was proposed to differentiate chronic lymphocytic leukemia (CLL) from other B‐cell non‐Hodgkin lymphomas (B‐NHLs). However, ambiguous immunophenotypes are common and remain a diagnostic challenge. Therefore, we evaluated the diagnostic benefit of measuring CD200 and CD43 expression together with the standard MS antigens. Methods: 138 lymphoma patient samples and a validation cohort of 138 additive samples were classified according to the standard MS and further assigned with one or two additional points, for high CD200 and/or CD43 expression levels. The " classical " MS and the " Matutes score‐extended " (MS‐e) were categorized as high (4‐5/6‐7), intermediate (2‐3/4‐5), and low (0‐1/0‐3). Samples were reclassified into the MS‐e with focus on ambiguous cases with an intermediate " classical " MS. Results: A total of 35 of 138 (25.4%) patient samples were assigned to the intermediate MS group and confirmed by histopathological reports as CLL (14/40.0%) and B‐NHLs other than CLL (21/60%). MS‐e analysis identified 13 of 14 (92.9%) of CLL cases (MS‐e 4–5) and 18/21 (85.7%) non‐CLL cases (MS‐e ≤ 3) correctly. Overall, the sensitivity of the CLL diagnosis was significantly increased by application of MS‐e compared to the " classical " MS (98.8% vs. 82.7%; p = 0.0009), while specificity of both methods was almost equal (94.7% vs. 98.3%; p = 0.4795). Of note, sole measurement of CD43 and CD200 on B‐cells sufficiently differentiated CLL from non‐CLL with a test accuracy superior to the " classical " MS (F1 score 96.2 vs. 93.6). Conclusion: CD200 and CD43 have a high informative value in diagnostic immunophenotyping and facilitate the separation of CLL from other B‐NHLs particularly in ambiguous cases.